2018
DOI: 10.1007/s10311-018-0791-y
|View full text |Cite
|
Sign up to set email alerts
|

Can the legacy of industrial pollution influence antimicrobial resistance in estuarine sediments?

Abstract: Antimicrobial resistance (AMR) represents a major global health threat, as well as a major hazard to sustainable economic development and national security. It remains, therefore, vital that current research aligns to policy development and implementation to alleviate a potential crisis. One must consider, for example, whether drivers of antibiotic resistance can be controlled in the future, or have they already accumulated in the past, whether from antibiotics and/or other pollutants? Unfortunately, industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 132 publications
(147 reference statements)
0
22
0
Order By: Relevance
“…In our study the uppermost sediments were 'jelly-like' in their composition and are constantly being washed which could reduce higher PTE concentrations in areas where there are reduced industrial inputs. This therefore has implications for a potential increase in antimicrobial resistance due to exposure of historical pollution at depth (Rodgers et al 2018). The time difference between our campaign and previous reports, particularly for Cr, shows the dynamic nature of the system with regard to complexity and elemental movement.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In our study the uppermost sediments were 'jelly-like' in their composition and are constantly being washed which could reduce higher PTE concentrations in areas where there are reduced industrial inputs. This therefore has implications for a potential increase in antimicrobial resistance due to exposure of historical pollution at depth (Rodgers et al 2018). The time difference between our campaign and previous reports, particularly for Cr, shows the dynamic nature of the system with regard to complexity and elemental movement.…”
Section: Discussionmentioning
confidence: 55%
“…The comparison showed that values from this study exceeded the geochemical baseline values and were more comparable to the Clyde Estuary baseline study results, suggesting that levels exceeding the baseline are likely affected by anthropogenic inputs. As previously reported, estuarine sediments in industrialised regions create environmentally stressful conditions for the sediment microbiome (Rodgers et al 2018); we therefore focussed on 'stressors' and concentrations above the threshold effect level (TEL) and probable effect level (PEL). The TEL represents the concentration below which adverse effects are unlikely to occur, whereas the PEL defines the level in which adverse effects are expected to occur (Macdonald et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of metals in the estuarine water is much lower than what is usually found in the Tinto River, which is probably the result of the dilution effect from seawater entry. Also, the higher pH of the water could trigger the precipitation of some metals (Rodgers et al, 2019). The higher concentration of phosphor in H1S versus H2S may be due to the input of phosphogypsum-rich wastewater from a nearby fertilizer plant (Sainz et al, 2004), which recently was shown to contaminate the estuary with heavy metals through a weathering process (Papaslioti et al, 2018).…”
Section: Discussion Environmental Conditions Of the Sampling Zonesmentioning
confidence: 99%
“…Higher MDR levels were found in isolates from sediments than from those in waters when considering all isolates from the estuary (H), or each individual zone (H1 or H2). This difference between phases could be due to the lower mobility of sediments and the possible accumulation of antibiotics, metals, or other pollutants (including ARGs) that may facilitate the selection of resistant bacterial populations, as has been proposed for other systems (Rodgers et al, 2019). Furthermore, the accumulation of resistant bacteria in sediments could facilitate bacterial cell contact; and, therefore, to increase the efficiency of HGT (Zhang et al, 2018).…”
Section: Mdr Levels and Profiles Diversity Among Ap R Bacterial Isolatesmentioning
confidence: 98%